Dimensions of Macroeconomic Uncertainty: A Common Factor Analysis - Steffen Henzel; Malte Rengel (Center for Economic Studies and ifo Institute (CESifo), 2014)
Uncertainty about the future course of the economy is a possible driver of aggregate fluctuations. To identify the different dimensions of uncertainty in the macroeconomy we construct a large dataset covering all types of economic uncertainty. We then identify two fundamental factors which account for the common dynamics in this dataset. These factors are interpreted as macroeconomic uncertainty. The first factor mainly captures business cycle uncertainty while the second factor is identified as oil and commodity price uncertainty. While both types of uncertainty foreshadow a decline in output, surprise increases in oil and commodity price uncertainty appear to be more important for fluctuations in real activity.
Keywords: C32; C38; E32; 330; macroeconomic uncertainty; factor model; aggregate fluctuations